Carbon nanofibers replacing graphene oxide in ceramic composites as a reinforcing-phase: Is it feasible?. Issue 12 (September 2017) - Cano-Crespo, Rafael; Moshtaghioun, Bibi Malmal; Gómez-García, Diego; Domínguez-Rodríguez, Arturo; Moreno, Rodrigo
Abstract: In recent years, the interest of graphene and graphene-oxide has increased extraordinarily due to the outstanding properties concurring in this material. In ceramic science, the possibility of combining excellent electrical conductivities together with an enhancement of mechanical properties has motivated the research in fabrication of graphene oxide-reinforced ceramic composites despite the intrinsic difficulties for sintering. In this work a comparison is made between graphene oxide-reinforced alumina composites and carbon nanofiber-reinforced alumina ones. It will be concluded that the improvement of mechanical properties is scarce, if any. Since carbon nanofibers have also a good electrical conductivity their importance for future applications as a replacement of more sophisticated but expensive graphene-based ceramic composites will be stressed.